2017
DOI: 10.1108/md-04-2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Patenting motives, technology strategies, and open innovation

Abstract: PurposeThe purpose of this study is to empirically investigate firms' motives to patent in general, and more specifically how some of these motives depend upon firms' technology strategies and especially their level of open innovation. Design/methodology/approachThe paper is based on a questionnaire survey sent to CTOs (or equivalent) of the largest R&D spenders among Swedish large firms (e.g., ABB, AstraZeneca, Ericsson, and Volvo) and among Swedish small and mediumsized enterprises. Principal component analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 87 publications
2
43
0
2
Order By: Relevance
“…Non-standard functions of patents, in general, hardly facilitate productive entrepreneurship, and often only serve rent-seeking. On the basis of an extensive literature review [cf., e.g., Langinier, 2005;Penin, 2005;Blind et al, 2006;2009;Chien, 2008;Noel, Schankerman, 2013;Grossmann et al, 2016;Förster, 2017;Holgersson, Granstrand, 2017], the following non-standard functions of patents can be distinguished: to block rivals, to use patents to increase someone's bargaining power in negotiations with potential business partners, to exploit a competitive advantage over rivals, to protect an enterprise's share in the domestic or international market, to increase the operating costs of the enterprise's rivals, to raise barriers to market entry, to mislead the enterprise's rivals in the patent race, and to force other enterprises to bear the expenses of a legal dispute over patent violation (patent predation strategy).…”
Section: The Links Between Patents and Leniency -Literature Reviewmentioning
confidence: 99%
“…Non-standard functions of patents, in general, hardly facilitate productive entrepreneurship, and often only serve rent-seeking. On the basis of an extensive literature review [cf., e.g., Langinier, 2005;Penin, 2005;Blind et al, 2006;2009;Chien, 2008;Noel, Schankerman, 2013;Grossmann et al, 2016;Förster, 2017;Holgersson, Granstrand, 2017], the following non-standard functions of patents can be distinguished: to block rivals, to use patents to increase someone's bargaining power in negotiations with potential business partners, to exploit a competitive advantage over rivals, to protect an enterprise's share in the domestic or international market, to increase the operating costs of the enterprise's rivals, to raise barriers to market entry, to mislead the enterprise's rivals in the patent race, and to force other enterprises to bear the expenses of a legal dispute over patent violation (patent predation strategy).…”
Section: The Links Between Patents and Leniency -Literature Reviewmentioning
confidence: 99%
“…Choe et al [7], based on data of patent citation, studied the flow of knowledge among organizations and the structural characteristics of the network. Although patents are closely linked to corporate innovation, it is noteworthy that not all technologies can be patented, given factors such as the degree of their innovation and strategic decisions of the enterprise [8,9,12,28,29].…”
Section: Analysis Of Citation Networkmentioning
confidence: 99%
“…In regard to product innovation value, Peter (2000) mentioned that, with the accumulation of organizational resources through R&D capability, an enterprise could satisfy product life cycle and market demands through new product performance, increase in product attribute, and new product R&D. Holgersson & Granstrand (2017) stated that an enterprise, by cultivating the capability of marketing service through organizational resources, could integrate tangible and intangible marketing service and channel systems and eff ectively promote new products to target customers. Yoon et al (2015) indicated that an enterprise, by developing the mass production capability through organizational resources, could reduce production costs, enhance operation process effi ciency, and promote product supply capability to product new products with innovation value.…”
Section: Research Hypothesismentioning
confidence: 99%